High-performance modified asphalt based on nanocomposite

By combining the nano powder with polyester material and optimizing compatibility in asphalt, the problem of difficulty in uniform dispersion of nanomaterials in asphalt is solved, and the high-temperature and low-temperature performance of modified asphalt is significantly improved.

CN119708870AActive Publication Date: 2025-03-28HUIZHOU SHENWAN TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510010830.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-03-28
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

Among the existing nanocomposite modified asphalts, nanomaterials are prone to spontaneous agglomeration due to their large specific surface area and high surface energy, and are difficult to disperse evenly in the asphalt, which limits its modification effect.

Method used

By pre-combining the nano powder with the polyester material, and using the lipophilicity and hydrogen bonds or polymeric bonds of the polyester for composite, the dispersion and compatibility of the nanomaterial in asphalt are optimized.

Benefits of technology

The high-temperature rutting resistance and low-temperature crack resistance of modified asphalt is significantly improved, and uniform dispersion and efficient modification of nanomaterials are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses high-performance modified asphalt based on a nano composite material, and belongs to the technical field of modified asphalt materials. The modified asphalt is characterized by comprising the following raw materials in parts by weight: 100 parts of matrix asphalt, 1.5-3 parts of SBS (Styrene Butadiene Styrene), 1-5 parts of hydroxylated modified nano powder composite polyester, 0.1-2 parts of a stabilizer and 0.01-0.5 part of a cross-linking agent. According to the invention, the nano-powder and the polyester material are compounded in advance through hydrogen bonds or polymeric bonds, good compatibility with SBS and asphalt is realized by using good lipophilicity of polyester, the dispersibility and compatibility of the powder in the asphalt are optimized, and the performance of the modified asphalt is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] High-performance modified asphalt based on nano-composite materials belongs to the technical field of modified asphalt materials. Background Art

[0002] In the field of road engineering, the performance improvement of asphalt materials has always been the focus of research. With the development of nanotechnology, nanocomposite modified asphalt has attracted widespread attention due to its unique physical and chemical properties. The high specific surface area and high activity of nanomaterials enable them to exhibit excellent performance in modified asphalt, including improving the high temperature stability, low temperature crack resistance and aging resistance of asphalt.

[0003] Chinese patent CN104559263A discloses a nano / polymer composite modified asphalt material and a preparation method thereof. The patent discloses a nano / polymer composite modified asphalt material composed of nano materials, polymers and matrix asphalt. This material combines nano ZnO, nano TiO2 or nano CaCO3 with polymers and matrix asphalt to provide a composite modified asphalt with good high temperature rutting resistance and low temperature crack resistance. However, this technology has serious deficiencies in actual use. Because nano materials are prone to spontaneous agglomeration due to their large specific surface area and high surface energy, they are difficult to be evenly dispersed in asphalt, which limits their effect on asphalt modification. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a high-performance modified asphalt based on a nanocomposite material in which nanomaterials are evenly dispersed.

[0005] The technical solution adopted by the present invention to solve its technical problem is: the high-performance modified asphalt based on nano-composite material is characterized in that the raw materials are composed of: 100 parts of base asphalt, 1.5-3 parts of SBS, 1-5 parts of hydroxylated modified nano powder composite polyester, 0.1-2 parts of stabilizer, and 0.01-0.5 parts of cross-linking agent in weight parts.

[0006] The present invention utilizes the high specific surface area and high activity of nanomaterials to react physically and chemically with asphalt to improve the high temperature rutting resistance and low temperature cracking resistance of modified asphalt. The present invention pre-compounds the nanomaterials with polyester materials through hydrogen bonds or polymer bonds, utilizes the good lipophilicity of polyester itself, achieves good compatibility with SBS and asphalt, optimizes the dispersibility and compatibility of the powder in asphalt, and achieves a significant improvement in the performance of modified asphalt.

[0007] Preferably, the raw materials are composed by weight: 100 parts of base asphalt, 2.0-2.5 parts of SBS, 2-4 parts of hydroxylated modified nano powder composite polyester, 0.5-1 part of stabilizer, and 0.1-0.2 part of cross-linking agent. Under the preferred composition by weight, the modified asphalt of the present invention exhibits more excellent comprehensive performance.

[0008] Optionally, the stabilizer in the present invention can use a common stabilizer modified by SBS, preferably a sulfur-containing compound stabilizer, such as diphenyl disulfide, difurfuryl disulfide, ethyl sulfide, di-n-octyltin dithioglycolate, and dimethyl dithioglycolate. These stabilizers form a stable colloidal system with the polymer and the asphalt by cross-linking and grafting reaction with the SBS polymer molecular chain and the active functional groups of the asphalt, thereby improving the thermal stability of the modified asphalt.

[0009] Specifically, the preparation method of the hydroxylated modified nano powder composite polyester is as follows: 1) The polyester comonomer is copolymerized under a catalyst and heating conditions to form a glue solution; 2) Keep heating, add 5%~10% of the mass of the hydroxylated modified nanopowder into the glue solution, and continue stirring for 2h~4h; 3) The product is obtained after removing impurities, washing, drying and forming.

[0010] The present invention uses polyester as a matrix to compound hydroxylated modified nano powder, directly adds hydroxylated modified nano powder into a reaction system for preparing polyester glue solution and continues the reaction, and forms hydrogen bonds or even polymerizes into ether bonds through the hydroxyl groups at the ends of polyester chains and the hydroxyl groups of hydroxylated modified nano powder for compounding, thereby obtaining a stable hydroxylated modified nano powder composite polyester.

[0011] Preferably, the comonomers described in step 1) are polyols, epichlorohydrin, and dianhydride, and the molar ratio of polyols, epichlorohydrin and dianhydride is 1:20~50:18~45. The present invention polymerizes epichlorohydrin and dianhydride into a polyester chain, and the polyester chain itself has high thermal stability, toughness and strength, which can meet the application requirements of asphalt materials. The polyester material uses polyols as initiators, and multiple polyester chains formed by copolymerization of epichlorohydrin and dianhydride are connected thereto, which can better form molecular entanglement with asphalt and SBS, and the thermal stability, toughness and strength of the modified asphalt are higher; and the ratio of epichlorohydrin monomer is controlled to be slightly higher than that of dianhydride, so that the chain end of the polyester chain is as hydroxyl as possible, which is easier to compound with hydroxylated modified nanopowder.

[0012] Preferably, the polyol is trimethylolethane, glycerol or pentaerythritol.

[0013] At the same time, these polyols can also be used as the crosslinking agent described in the weight composition of the modified asphalt of the present invention.

[0014] Preferably, the dianhydride is tetrabromophthalic anhydride, phthalic anhydride, 1,8-naphthalene anhydride or succinic anhydride. More preferably, it is tetrabromophthalic anhydride or phthalic anhydride. The polyester obtained by copolymerization of the preferred dianhydride has better thermal stability, toughness and strength.

[0015] Preferably, in step 1), the catalyst is sodium methoxide or sodium ethoxide, the heating condition is heating to 50°C to 90°C, and the reaction time is 4h to 8h. The preferred catalyst and reaction temperature can ensure the smooth progress of the above copolymerization reaction. The reference range of the molar ratio of the catalyst to the polyol is 0.0001 to 0.001:1.

[0016] More specifically, the preparation method of the hydroxylated modified nanopowder is as follows: adding nanopowder to a NaOH aqueous solution with a concentration of 5 mol / L to 10 mol / L, wherein the mass ratio of the NaOH aqueous solution to the nanopowder is 100:1 to 5, heating to 120°C to 140°C for hydrothermal synthesis, and the hydrothermal synthesis time is 20h to 30h; the product after hydrothermal synthesis is repeatedly washed with water and acid washed, and then dried and ground.

[0017] The present invention provides a simple method for preparing hydroxylated modified nanopowder. Since the present invention does not require high-density hydroxylation modification of the nanopowder, the simple modification method can be used to prepare hydroxylated modified nanopowder efficiently and at low cost, and can adapt to the large-scale use of modified asphalt.

[0018] Preferably, the nano powder includes one or more of nano ZnO, nano TiO2 and nano CaCO3.

[0019] Preferably, in the preparation method of the hydroxylated modified nanopowder, the material is stirred at room temperature for 60 min to 100 min before the hydrothermal synthesis. Pre-stirring at room temperature helps to pre-disperse the nanopowder in water and uniformly carry out the subsequent hydrothermal synthesis reaction, thereby improving the consistency and quality of the product and reducing the agglomeration phenomenon during the hydrothermal synthesis process, thereby obtaining finer and more uniform nanoparticles.

[0020] The preparation steps of the above-mentioned high-performance modified asphalt based on nanocomposite materials are as follows: 1) Mixing the hydroxylated modified nano-powder composite polyester and the cross-linking agent at 200° C. to 250° C. according to the ratio to obtain a premix; 2) Heat the base asphalt, SBS, stabilizer and premix to 170℃~180℃ according to the proportion, stir and mix, then shear with a high-speed shearing machine for 50min~90min, cool and store, and then develop for 1h~2h.

[0021] Stirring the mixed raw materials at a temperature of 200°C to 250°C can promote the cross-linking reaction and increase the cross-linking density of the material. The base asphalt, SBS (styrene-butadiene-styrene block copolymer), stabilizer and premix are mixed according to the proportion and heated to 170°C to 180°C. This temperature is conducive to the compatibility of SBS and asphalt, and can also ensure the effective effect of the stabilizer. Shearing the mixture with a high-speed shearing machine helps to further disperse the nanomaterials and SBS, improve the uniformity of the mixture, and enhance the stability and performance of the modified asphalt. This process can produce high-performance modified asphalt with excellent high and low temperature performance, anti-aging performance and durability, which is suitable for various harsh road engineering environments.

[0022] Preferably, the stirring and mixing in step 1) is carried out in a twin-screw extruder; and the speed of the high-speed shearing machine in step 2) is 600-800 rpm. Using a twin-screw extruder for stirring and mixing and controlling the speed of the high-speed shearing machine can improve the preparation efficiency and product quality of the modified asphalt, reduce production costs, and ensure the consistency and uniformity of the product.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides a high-performance modified asphalt technology based on nano-composite materials, which optimizes the dispersibility and compatibility of nano-materials in asphalt by compounding nano-powders with polyester materials in advance, and significantly improves the high-temperature rutting resistance and low-temperature cracking resistance of the modified asphalt. A simple hydroxylation-modified nano-powder preparation method is adopted to achieve high-efficiency, low-cost large-scale production, and the use of sulfur-containing compound stabilizers improves thermal stability. The preferred raw material ratio and preparation conditions further improve the comprehensive performance of the modified asphalt. In addition, the use of a twin-screw extruder and controlling the speed of a high-speed shearing machine improves production efficiency, reduces costs, and ensures product consistency and uniformity. The modified asphalt of the present invention is not only suitable for various harsh road engineering environments, but also has environmental and economic benefits, providing a solution for road construction with longer service life and lower maintenance costs. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with specific examples, wherein Example 1 is the best example. The following raw materials are all commercially available.

[0025] Preparation of hydroxylated modified nano ZnO Nano ZnO was added to a 7 mol / L NaOH aqueous solution, the mass ratio of the NaOH aqueous solution to the nano ZnO was 100:3, the material was first stirred at room temperature for 80 min, and then heated to 130° C. for hydrothermal synthesis, and the hydrothermal synthesis time was 25 h; the product after hydrothermal synthesis was repeatedly washed with water and acid washed, and then dried and ground.

[0026] Preparation of Hydroxylation-Modified Nano-TiO2 Nano-TiO2 was added to a 5 mol / L NaOH aqueous solution, the mass ratio of the NaOH aqueous solution to nano-TiO2 was 100:5, the material was first stirred at room temperature for 100 min, and then heated to 120°C for hydrothermal synthesis, and the hydrothermal synthesis time was 20 h; the product after hydrothermal synthesis was repeatedly washed with water and acid washed, and then dried and ground.

[0027] Preparation of hydroxylated modified nano-CaCO3 Nano-CaCO3 was added to a 10 mol / L NaOH aqueous solution, the mass ratio of the NaOH aqueous solution to the nano-CaCO3 was 100:1, the material was first stirred at room temperature for 60 min, and then heated to 140°C for hydrothermal synthesis, and the hydrothermal synthesis time was 30 h; the product after hydrothermal synthesis was repeatedly washed with water and acid washed, and then dried and ground.

[0028] Preparation of Hydroxylation-modified Nano-TiO2 Composite Polyester A 1) Add glycerol, epichlorohydrin, tetrabromophthalic anhydride and sodium methoxide in a molar ratio of 1:35:30:0.0005 into a polymerization kettle, start stirring and heat to 65°C for copolymerization for 6 hours to prepare a glue solution; 2) Keep heating, add 8% of the mass of the prepared hydroxylated modified nano-TiO2 into the glue solution, and continue stirring for 3 hours; 3) The product is obtained after removing impurities, washing, drying and forming.

[0029] Preparation of Hydroxylation-modified Nano-TiO2 Composite Polyester B 1) Add glycerol, epichlorohydrin, succinic anhydride and sodium methoxide in a molar ratio of 1:35:30:0.0005 into a polymerization kettle, start stirring and heat to 65°C for copolymerization for 6 hours to prepare a glue solution; 2) Keep heating, add 8% of the mass of the prepared hydroxylated modified nano-TiO2 into the glue solution, and continue stirring for 3 hours; 3) The product is obtained after removing impurities, washing, drying and forming.

[0030] Preparation of hydroxylated modified nano ZnO composite polyester 1) Add trimethylolethane, epichlorohydrin, phthalic anhydride and sodium methoxide in a molar ratio of 1:20:18:0.0001 into a polymerization kettle, start stirring and heat to 90°C for copolymerization for 4 hours to prepare a glue solution; 2) Keep heating, add 5% of the mass of the prepared hydroxylated modified nano ZnO into the glue solution, and continue stirring for 2 hours; 3) The product is obtained after removing impurities, washing, drying and forming.

[0031] Preparation of Hydroxylation-modified Nano-CaCO3 Composite Polyester 1) Add pentaerythritol, epichlorohydrin, 1,8-naphthalene anhydride and sodium ethoxide into a polymerization kettle at a molar ratio of 1:50:45:0.001, start stirring and heat to 50°C for copolymerization reaction for 8 hours to prepare a glue solution; 2) Keep heating, add 10% of the mass of the prepared hydroxylated modified nano-CaCO3 into the glue solution, and continue stirring for 4 hours; 3) The product is obtained after removing impurities, washing, drying and forming. Example 1

[0032] Prepare the following materials by weight: 100 parts of base asphalt, 2.2 parts of SBS, 3 parts of the prepared hydroxylated modified nano ZnO composite polyester A, 0.8 parts of diphenyl disulfide, and 0.15 parts of pentaerythritol.

[0033] 1) Feeding the hydroxylated modified nano ZnO composite polyester A and pentaerythritol into a twin-screw extruder, controlling the mixing temperature at 230°C, and discharging the materials to obtain a premix; 2) Heat the base asphalt, SBS, diphenyl disulfide and premix to 175°C according to the proportion, stir and mix, and then shear for 70 minutes with a high-speed shearing machine at a speed of 700 rpm; cool and store, and then develop for 1.5 hours. Example 2

[0034] Prepare the following materials by weight: 100 parts of base asphalt, 2.2 parts of SBS, 3 parts of the prepared hydroxylated modified nano ZnO composite polyester B, 0.8 parts of diphenyl disulfide, and 0.15 parts of pentaerythritol.

[0035] 1) Feeding the hydroxylated modified nano ZnO composite polyester B and pentaerythritol into a twin-screw extruder, controlling the mixing temperature at 230°C, and discharging the materials to obtain a premix; 2) Heat the base asphalt, SBS, diphenyl disulfide and premix to 175°C according to the proportion, stir and mix, and then shear for 70 minutes with a high-speed shearing machine at a speed of 700 rpm; cool and store, and then develop for 1.5 hours. Example 3

[0036] Prepare the following materials by weight: 100 parts of base asphalt, 2.0 parts of SBS, 2 parts of the prepared hydroxylated modified nano ZnO composite polyester A, 0.5 parts of diphenyl disulfide, and 0.1 parts of pentaerythritol.

[0037] 1) Feeding the hydroxylated modified nano ZnO composite polyester A and the crosslinking agent into a twin-screw extruder, controlling the mixing temperature at 220°C, and discharging the material to obtain a premix; 2) Heat the base asphalt, SBS, stabilizer and premix to 175°C according to the proportion, stir and mix, and then shear for 80 minutes with a high-speed shearing machine at a speed of 700 rpm; cool and store, and then develop for 1.5 hours. Example 4

[0038] Prepare the following materials by weight: 100 parts of base asphalt, 2.5 parts of SBS, 4 parts of the prepared hydroxylated modified nano ZnO composite polyester A, 1 part of diphenyl disulfide, and 0.2 parts of pentaerythritol.

[0039] 1) Feeding the hydroxylated modified nano ZnO composite polyester A and the crosslinking agent into a twin-screw extruder, controlling the mixing temperature at 240°C, and discharging the material to obtain a premix; 2) Heat the base asphalt, SBS, stabilizer and premix to 175℃ according to the proportion, stir and mix, and then shear for 60 minutes with a high-speed shearing machine at a speed of 700 rpm; cool and store, and then develop for 1.5 hours. Example 5

[0040] Prepare the following materials by weight: 100 parts of base asphalt, 1.5 parts of SBS, 5 parts of the prepared hydroxylated modified nano ZnO composite polyester, 0.1 parts of ethyl sulfide, and 0.5 parts of trimethylolethane.

[0041] 1) feeding the hydroxylated modified nano-powder composite polyester and the cross-linking agent into a twin-screw extruder, controlling the mixing temperature at 200°C, and discharging the materials to obtain a premix; 2) Heat the base asphalt, SBS, stabilizer and premix to 170℃ according to the proportion, stir and mix, and then shear for 90 minutes with a high-speed shearing machine at a speed of 600 rpm; cool and store, and then develop for 2 hours. Example 6

[0042] Prepare the following materials by weight: 100 parts of base asphalt, 3 parts of SBS, 1 part of the prepared hydroxylated modified nano-CaCO3 composite polyester, 2 parts of isooctyl tin dimethyl dimercaptoacetate, and 0.01 parts of pentaerythritol.

[0043] 1) Feeding the hydroxylated modified nano-powder composite polyester and the cross-linking agent into a twin-screw extruder, controlling the mixing temperature at 250°C, and discharging the material to obtain a premix; 2) Heat the base asphalt, SBS, stabilizer and premix to 180℃ according to the proportion, stir and mix, and then shear with a high-speed shearing machine for 50 minutes at a speed of 800 rpm; cool and store, and then develop for 1 hour.

[0044] Comparative Example 1 The raw material formula and process are basically the same as those in Example 1, except that pentaerythritol as a cross-linking agent is not added to the raw materials.

[0045] Comparative Example 2 The raw material formula and process are basically the same as those in Example 1, except that SBS and diphenyl disulfide as a stabilizer are not added to the raw materials.

[0046] Comparative Example 3 The raw material formula and process are basically the same as those in Example 1, except that no premix is ​​prepared first during the preparation process, but the raw materials are directly stirred and mixed in step 2).

[0047] The heat aging test and BBR test were carried out on each embodiment and comparative example. The experimental results are shown in Table 1 and Table 2 respectively.

[0048] Table 1 Heating aging test results

[0049] It can be seen from Table 1 that the modified asphalt of the embodiment of the present invention has good anti-aging performance, and the formula and method of the present invention significantly improve the anti-aging performance of the base asphalt.

[0050] Table 2 BBR test results

[0051] It can be seen from Table 1 that the modified asphalt of the embodiment of the present invention significantly improves the low temperature performance of the base asphalt.

[0052] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A high performance modified asphalt based on nanocomposite material, characterized in that: The raw materials include, by weight: 100 parts of base asphalt, 1.5-3 parts of SBS, 1-5 parts of hydroxylated modified nano powder composite polyester, 0.1-2 parts of stabilizer, and 0.01-0.5 parts of cross-linking agent.

2. The high performance modified asphalt based on nanocomposite material according to claim 1, characterized in that: The raw materials are composed of 100 parts by weight of base asphalt, 2.0-2.5 parts of SBS, 2-4 parts of hydroxylated modified nano powder composite polyester, 0.5-1 part of stabilizer, and 0.1-0.2 part of cross-linking agent.

3. The high performance modified asphalt based on nanocomposite material according to claim 1 or 2, characterized in that: The preparation method of the hydroxylated modified nano powder composite polyester is as follows: 1) The polyester comonomer is copolymerized under a catalyst and heating conditions to form a glue solution; 2) Keep heating, add 5%~10% of the mass of the hydroxylated modified nanopowder into the glue solution, and continue stirring for 2h~4h; 3) The product is obtained after removing impurities, washing, drying and forming.

4. The high performance modified asphalt based on nanocomposite material according to claim 3, characterized in that: In step 1), the comonomers are polyols, epichlorohydrin and dianhydride, and the molar ratio of polyols, epichlorohydrin and dianhydride is 1:20-50:18-48.

5. The high performance modified asphalt based on nanocomposite material according to claim 4, characterized in that: In step 1), the catalyst is sodium methoxide or sodium ethoxide, and the heating condition is heating to 50°C to 90°C.

6. The high performance modified asphalt based on nanocomposite material according to claim 3, characterized in that: The preparation method of the hydroxylated modified nano powder is as follows: adding nano powder to a NaOH aqueous solution with a concentration of 5 mol / L to 10 mol / L, wherein the mass ratio of the NaOH aqueous solution to the nano powder is 100:1 to 5, heating to 120° C. to 140° C. for hydrothermal synthesis, wherein the hydrothermal synthesis time is 20 h to 30 h; and the product after the hydrothermal synthesis is repeatedly washed with water and acid washed, and then dried and ground to obtain the product.

7. The high performance modified asphalt based on nanocomposite material according to claim 6, characterized in that: The nano powder includes one or more of nano ZnO, nano TiO2 and nano CaCO3.

8. The high performance modified asphalt based on nanocomposite material according to claim 6, characterized in that: Before the hydrothermal synthesis, the materials are stirred at room temperature for 60 min to 100 min.

9. The high performance modified asphalt based on nanocomposite material according to claim 1 or 2, characterized in that: The preparation steps are: 1) Mixing the hydroxylated modified nano-powder composite polyester and the cross-linking agent at 200° C. to 250° C. according to the ratio to obtain a premix; 2) Heat the base asphalt, SBS, stabilizer and premix to 170℃~180℃ according to the proportion, stir and mix, then shear with a high-speed shearing machine for 50min~90min, cool and store, and then develop for 1h~2h.

10. The high performance modified asphalt based on nanocomposite material according to claim 9, characterized in that: The stirring and mixing in step 1) is carried out in a twin-screw extruder; the rotation speed of the high-speed shearing machine in step 2) is 600-800 rpm.

Citation Information

Patent Citations

  • Nano / polymer compound modified asphalt material and preparation method thereof

    CN104559263A

  • Epoxy modified asphalt and preparation method thereof

    CN106832980A

  • Nano composite modified asphalt and preparation method thereof

    CN110396300A

  • Nano modified asphalt and preparation method thereof

    CN110499036A

  • High-viscosity modified asphalt and preparation method thereof

    CN116790129A